Invasive pulmonary aspergillosis and pulmonary tuberculosis in a patient treated with infliximab for Crohn's disease. (2019) - Buonomo, Antonio Riccardo; Viceconte, Giulio; Compare, Debora; Vargas, Maria; Iacovazzo, Carmine; Zappulo, Emanuela; Nardone, Gerardo; Servillo, Giuseppe; Borgia, Guglielmo; Gentile, Ivan
Highlights: Pulmonary TB together with invasive pulmonary aspergillosis due to infliximab therapy has been occasionally described. Other than tuberculosis reactivation, TNF-α antagonists may be associated with other opportunistic infections such as invasive aspergillosis. Interactions among rifamycins, antifungal and antiarrhythmic drugs are complex and may require the choice of second line therapies. Isavuconazole may have a better interaction profile with amiodarone and antitubercular therapy than voriconazole. Abstract: We report a case of concurrent development of active pulmonary tuberculosis and invasive pulmonary aspergillosis (IPA) in a patient who received therapy with infliximab for Crohn's disease. He has been treated with antitubercular therapy and liposomal amphotericin B for 8 weeks. His clinical course was complicated by paroxysmal atrial fibrillation requiring maintenance therapy with amiodarone, respiratory failure due both to pneumonia caused by methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamases (ESBL)-producing Klebsiella pneumoniae and pleural effusion requiring chest drainage. At discharge, a maintenance regimen based on the administration of isavuconazole 200 mg daily, moxifloxacin 400 mg daily and isoniazid 300 mg daily was chosen to avoid multiple drug-drug interaction between rifamycins, antifungal triazole agents and antiarrhythmic drugs. At 3 months of follow-up his clinical conditions were dramatically improved, high resolution chest tomography (HRCT) showed reduction of parenchymal lesions and no changes both in sinus rhythm and QTc interval were noticed. Besides the complexity and the peculiarity of the clinical scenario, this case underlines the risk of invasive fungal infections linked to the administration of TNF-α antagonists in gastroenterological setting and the importance of accurate evaluation of drug-drug interactions when choosing the antimicrobial therapies.